The death of the left why we must begin from the beginning again - Winlow, Simon 1972-; Hall, Steve 1955- (Policy Press, 2023)
Winlow and Hall argue that the only way to resurrect leftist politics is to begin from the beginning again. They identify the root causes of its maladies, describe how new cultural obsessions displaced core unifying principles, and outline how a new reincarnation of the left can win in the 21st century
Also issued in print: 2023. - Includes bibliographical references and index
Keywords: Right and left (Political science); Culture conflict / Political aspects